2000
DOI: 10.2307/177445
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding Effects on Resistance and Transmission-Related Traits in the Silene-Microbotryum Pathosystem

Abstract: Abstract. Inbreeding in local host populations will be a common phenomenon in hostpathogen systems that are characterized by metapopulation dynamics, i.e., frequent extinction and recolonization of local host populations by small numbers of founding individuals. As an example of a pathosystem with metapopulation dynamics we investigated the impact of inbreeding in the host plant Silene alba on its interaction with the anthersmut fungus Microbotryum violaceum. Seeds from eight populations of S. alba were sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(105 citation statements)
references
References 38 publications
8
97
0
Order By: Relevance
“…Ouborg et al (2000) found that inbreeding in the perennial plant Silene alba resulted in increased resistance to anther-smut fungus in some lines and decreased resistance in others. Similarly, Stevens et al (1997) found that some inbred lines of flour beetles Tribolium castaneum were more susceptible than others to tapeworm parasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ouborg et al (2000) found that inbreeding in the perennial plant Silene alba resulted in increased resistance to anther-smut fungus in some lines and decreased resistance in others. Similarly, Stevens et al (1997) found that some inbred lines of flour beetles Tribolium castaneum were more susceptible than others to tapeworm parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, some empirical studies have found evidence for inbreeding depression in resistance traits of the host (Potts et al 1994;Coltman et al 1999;Ouborg et al 2000). Hence, susceptibility may be seen as a component of inbreeding depression (Charlesworth and Charlesworth 1987).…”
mentioning
confidence: 99%
“…Outcross progeny of the perennial Erigeron glaucus supported fewer thrips (Apterothrips apteris) than self progeny only if the self progeny were derived from a parent that already supported high number of thrips (presumably a low resistance genotype) and the cross-pollination sire supported few thrips (presumably a high resistance genotype; Strauss and Karban 1994). In a plant-pathogen system, Ouborg et al (2000) found that active resistance of the highly outcrossing perennial Silene alba to the fungus Microbotryum violaceum was altered by inbreeding. The effect of inbreeding was variable among lines and among populations, in some cases increasing resistance, in others decreasing resistance.…”
Section: Inbreeding and Herbivorymentioning
confidence: 99%
“…In particular, work on Linum marginale and its rust pathogen, Melampsora lini (eg Jarosz and Burdon, 1991;Thrall et al, 2001), and studies of Silene alba and its anther smut fungus, Microbotryum violaceum (eg Alexander and Antonovics, 1995;Ouborg et al, 2000), have greatly advanced the field. Studies in noncrop plant populations of bacterial pathogens (eg Kover and Schaal, 2002) are much rarer.…”
Section: Introductionmentioning
confidence: 99%